2016
DOI: 10.22456/1679-9216.84475
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma in a Pig

Abstract: Background: Squamous cell carcinoma (SCC) is a malignant neoplasm of epidermal cells that exhibits keratinocyte differentiation. These neoplasms are common in dogs, cats, horses, and cattle, relatively uncommon in sheep, and rarely affect goats and pigs. There are several factors that are associated with the development of SCC, including prolonged exposure to ultraviolet light, lack of pigment in the epidermis, and sparse coating or lack of fur at the affected sites. The aim of this study was to report the occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…40,46,55 Growing evidence has suggested that equus caballus papillomavirus type 2 (EcPV2) is likely the etiological cause of equine SCCs, including penile and preputial SCC, 40,46 as well as equine vulvo-vaginal carcinoma. 35,38,46,55 In the last decade, numerous studies have investigated the prevalence and the possible role of EcPV2 in inducing penile and preputial epithelial preneoplastic lesions and both benign and malignant tumors. 46 However, the role of EcPV2 in the pathogenesis of genital lesions in mares remains elusive.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…40,46,55 Growing evidence has suggested that equus caballus papillomavirus type 2 (EcPV2) is likely the etiological cause of equine SCCs, including penile and preputial SCC, 40,46 as well as equine vulvo-vaginal carcinoma. 35,38,46,55 In the last decade, numerous studies have investigated the prevalence and the possible role of EcPV2 in inducing penile and preputial epithelial preneoplastic lesions and both benign and malignant tumors. 46 However, the role of EcPV2 in the pathogenesis of genital lesions in mares remains elusive.…”
mentioning
confidence: 99%
“…46 However, the role of EcPV2 in the pathogenesis of genital lesions in mares remains elusive. 17,35,38,43,55 Similar to the equine male counterpart, vulvo-vaginal carcinoma represents a malignant tumor that can occur with a de novo onset or arise from precursor lesions, such as plaques and papillomas. 52,53 Recently, different equine SCCs have been reported to undergo the epithelial-to-mesenchymal transition (EMT) process.…”
mentioning
confidence: 99%
“…2 -4 Oral and cutaneous squamous cell carcinomas have been infrequently reported in pot-bellied pigs kept as pets and may occur in farm pigs as well. 6- 11…”
mentioning
confidence: 99%
“…[2][3][4] Oral and cutaneous squamous cell carcinomas have been infrequently reported in pot-bellied pigs kept as pets and may occur in farm pigs as well. [6][7][8][9][10][11] In animals and humans, including swine, there is an association between squamous cell carcinoma and ultraviolet (UV) light exposure. 9,[12][13][14] This was considered unlikely in this case, as this animal was housed indoors at both the breeding facility and the research facility and thus not exposed to UV light.…”
mentioning
confidence: 99%
See 1 more Smart Citation